2003
DOI: 10.1108/01443570310486338
|View full text |Cite
|
Sign up to set email alerts
|

The implications of fit between planning environments and manufacturing planning and control methods

Abstract: The applicability of manufacturing planning and control methods differs between environments. This paper explains the fit between the planning environment and material and capacity planning on the detailed material planning and shop-floor planning levels. The study is based on a conceptual discussion and a survey of 84 Swedish manufacturing companies. Results show the use of planning methods and their levels of user satisfaction in complex customer order production, configure to order production, batch product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 22 publications
1
109
1
3
Order By: Relevance
“…To structure the variables, they are by Olhager and Rudberg [39] grouped in three categories; product related, market related and manufacturing process related. Jonsson and Mattsson [2] and Schönsleben [40] do a similar grouping of the environmental variables.…”
Section: Implications Of the Production Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…To structure the variables, they are by Olhager and Rudberg [39] grouped in three categories; product related, market related and manufacturing process related. Jonsson and Mattsson [2] and Schönsleben [40] do a similar grouping of the environmental variables.…”
Section: Implications Of the Production Environmentmentioning
confidence: 99%
“…The implications of the production environment for the fit of planning methods and the design and selection of production planning and control systems have been widely studied, and the applicability of PPC methods have been found to differ between production environments [2]. There is no one-size fits all approach to PPC, thus the characteristic features describing the production environment must be considered when designing the PPC system [2].…”
Section: Implications Of the Production Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, from Kingsman's (2000) argument above it follows that dispatching may be the least important stage in the planning and control hierarchy for MTO companies. Jonsson & Mattsson (2003) agreed with this, but also suggested implementing a 'dispatching list' method, where advised priorities are given to the shop floor. On planning for the use of capacity at the dispatching level, Tenhiälä (2011) concluded that rough-cut methods -as featured in many ERP systems -can be used by companies utilising job-shop environments (i.e.…”
Section: Mto Requirements and Erp Functionality At The Shop Floor Dismentioning
confidence: 99%